Nudity of Male and Female Characters in Television Advertising Across 13 Countries. (December 2020) - Matthes, Jörg; Prieler, Michael
There is a lack of comparative research on nudity in television advertising. Building on cross-cultural theory, we examined countries' gender indices and preclearance policies as predictors of nudity. We also tested the influence of a main actors' gender and age, as well as the role of product categories. We sampled N = 1, 755 TV ads from 13 countries and found that the main characters' nudity was higher for women compared with men, less likely with increasing age, and occurred more often for congruent than incongruent products. Multilevel analyses showed that nudity was independent of a country's gender indices and preclearance policy.